Information and Analytical Support of Financial Controlling of Joint Activities of Business Entities (Economics and region, 2020)
The peculiarities of the formation and circulation of controlling financial information are analyzed, its essence is determined, the peculiarities of the information space functioning of joint activity are substantiated and measures to improve the circulation of management data between participants of joint activity and separate centers of their production within the current economic structure are developed. To deepen the scientific basis of the study of the origin and circulation of financial controlling information in joint activities considered the essence and content of the category "information space of controlling information", which allowed to identify the main centers of its production and identify specific features of different types of controlling information and their role in the process enterprise management.  It is proposed to consider the information space of controlling information as a single medium of data circulation on various components of development of a separate business entity.
Keywords: controlling; financial control; planning; management; , joint venture; joint activity